The republic of kazakhstan and revival of «New silk road» - Сергaзин, Е. Ф. (Journal of Oriental Studies, 2017)
«New Silk Road project is mutually beneficial and relevant to globalization trends for both Central Asia and Europe. New Silk Road has a number of strategic advantages that can contribute to unity of the countries of Eurasian Continent and to achieving their economic potential».